HUBUNGAN KARAKTERISTIK, PENGETAHUAN DAN SIKAP KEPALA KELUARGA TENTANG RUMAH SEHAT TERHADAP INFEKSI SALURAN PERNAFASAN AKUT (ISPA) DI WILAYAH KERJA PUSKESMAS MEDANG KAMPAI KELURAHAN TELUK MAKMUR KECAMATAN MEDANG KAMPAI KOTA DUMAI TAHUN 2014 - reni indra aristi; irnawati marsaulina; taufik ashar (Lingkungan dan Kesehatan Kerja, 2014)
ABSTRACT House is one of principal need of the human being in addition to food and cloth. Construction of house and it environment that did not based to the health requirement is a risk factor of thr transmission of any diseases one of them is acute upper respiratory track. The objective of this research is to study factors related to the ISPA in urban village of Teluk Makmur sub-district of Medang Kampai, Dumai in 2014. This research is cross sectional study. The number of sample is 71 households by simple random sampling. The data is collected by using questionnaire and direct observation. The univarian data is analyzed by descriptive study and bivariance data is analyzed by Chi Square test and Fisher Exact test with Confidential level 95%. The research indicated that the proportion of head of householdis in the age < 38 years old for 41 person (57.7%), the high education for 37 persons (52.1%), have work for 54 person (76.1%), has income < IDR 1.700.000 for 40 persons (56.3%), smoking in home for 54 persons (76.1%), has a good knowledge for 50 persons (70.4%), has a good attitude for 42 persons (59.2%), unhealthy house of 45 units (63.4%), the destiny of bad room is 51 unit (71.8%) and patient with ISPA for 56 persons (78.9%). The results of bivarian indicated that there is significant correlation between smoking in house (p=0.001), knowledge (p=0.004), attitude (p=0.005), unhealthy house (p=0.001) and density of bedroom (p=0.004) with ISPA. It is suggested to the health staff of puskesmas Medang Kampai Dumai to increase the health extension of a health house and treatment of ISPA. Keywords : Characteristic, Knowledge, Attitude, Health House, ISPA